Separation and Lithological Mapping of PFAS Mixtures in the Vadose Zone at a Contaminated Site - Bekele, Dawit N.; Liu, Yanju; Donaghey, Mark; Umeh, Anthony; Arachchige, Chamila S. V.; Chadalavada, Sreenivasulu; Naidu, Ravi (Frontiers in Water, 2020)
Perfluoroalkyl and polyfluoroalkyl substances (PFAS) are persistent organic contaminants of concern to human and environmental health. Several literature reviews and laboratory column experiments have been conducted to determine the transport parameters and to describe the fate of PFAS as they migrate in subsurface environments. However, there are very few case studies focusing on contaminated sites with high-resolution field data. Such studies are crucial for the validation of transport simulation models that have been developed from experimental studies, prior to their broader applications. The key purpose of this research was to evaluate lithological separations of PFAS fractions as they are transported in the vadose zone of a historically (1979) contaminated where Aqueous Film Forming Foam (AFFF) formulations (3M LightwaterTM and AnsuliteTM) have been used for fire training exercises. Surface and subsurface soils and groundwater samples were collected across the site and a total of 29 PFAS compounds were selected as target analytes. The results indicated a distinct profile of PFAS concentration with depth at most of the test bores, exhibiting separation of PFAS as transported in vadose zone soils. Perfluorooctanoic acid (PFOA), Perfluorooctane sulfonic acid (PFOS) and Perfluorohexane sulfonic acid (PFHxS) were the predominant compounds detected in the site samples and they have been found in near-surface soils (< 3 m) with concentrations declining with depth. The concentration of the 6:2 fluorotelomer sulfonate showed little change with depth in most of the test bore wells. The percentage concentration of each compound relative to the sum of PFAS, and the ratio of PFHxS/PFOS with depth, suggested transformation processes. Despite the relatively high solubility of PFAS, and that the application of AFFF has been ceased for some years at the site, there were still significant concentrations of PFAS adsorbed to the vadose zone soils that acted as ongoing sources of contamination to groundwater.